Steamboats LIGHTNING and TYRRELL at a boat landing, Klondike City, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Klondike City was a small settlement across the Klondike River from Dawson. Caption on image: "Klondyke City" Original image in Hegg Album 16, page 47. Original photograph by Eric A. Hegg 308; copied by Webster and Stevens 114.A. Klondike Gold Rush.